Using Artificial Intelligence to Develop a Mentorship Map - Conner, Laneshia; Scoresby, Kristel; Watts, Keith J. (The journal of faculty development, 2025)
Academic mentorship is essential for faculty development, yet mid-career researchers have limited resources. This study explores AI-assisted mentorship models using biosketch analysis, AI mapping, and human expertise to enhance mentor selection. Tools like Google NotebookLM and Mural streamlined coding, visualization, and theme identification, improving alignment with mentees' research goals. Findings suggest AI can optimize mentorship processes, offering broader applications for research efficiency and faculty development. Despite minor limitations, AI provides a scalable framework for enhancing academic mentorship.